Experimental and numerical simulation study on microstructure, residual stress and mechanical properties of Fe–Mn–C–Cr cryogenic high-manganese steel arc-welded joint - Jiang Yang; Honggang Dong; Guangfeng Wu; Feng Xiong (Journal of Materials Research and Technology)
Novel Fe–23Mn-0.45C-3.5Cr cryogenic steel welded joint was fabricated by a gas metal arc welding process. To determine the reason for the degraded impact toughness in heat-affected zone (HAZ), the microstructure and carbide precipitates were investigated. The residual stress of welded joint was also calculated, measured and verified, respectively. The results reveal that abnormal grain growth occurred in HAZ, and the average grain size of base metal and HAZ is about 36.9 μm and 103.8 μm, respectively, but there was no phase transformation. A large number of continuous lamellar or rod-shaped precipitates with a size of 200 nm × 60 nm, identified as Cr23C6 carbides, can be observed along the grain boundary in HAZ. On this basis, the formation mechanism of carbides precipitated at the grain boundary in HAZ was analyzed. In addition, a high tensile residual stress is about 520 MPa appeared in HAZ, which gradually decreased with increasing distance from the fusion line. The microhardness of HAZ had a similar trend to the residual stress, but it was higher than that of the base metal. The impact toughness of HAZ was significantly lower than that of base metal, which increased with increasing distance from the fusion line. This was mainly attributed to the welding residual stress and the precipitation of carbides in HAZ.